Medical monopoly : intellectual property rights and the origins of the modern pharmaceutical industry - Gabriel, Joseph M. (Joseph Michael) (Chicago : The University of Chicago Press, 2014)
"Drawing on a wealth of previously overlooked archival material, 'Medical Monopoly' combines legal, medical, and business history to offer a sweeping new interpretation of the origins of the complex and often troubling relationship between the pharmaceutical industry and medical practice today. Joseph M. Gabriel provides the first detailed history of patent and trademark law as it relates to the nineteenth century pharmaceutical industry, as well as unique interpretation of medical ethics, therapeutic reform, and efforts to regulate the market in pharmaceuticals before World War I"--Jacket.
Medical science and property rights in the early republic -- Monopoly and ethics in the antebellum years -- In the shadow of war -- Therapeutic reform and the reinterpretation of monopoly -- The ambiguities of abundance -- The embrace of intellectual property -- Conclusion : The promise of reform.
Includes bibliographical references (pages 255-324) and index.
Keywords: Pharmaceutical policy -- United States -- History; Drug development -- United States -- History; Drugs -- Law and legislation -- United States; Pharmacy -- Law and legislation -- United States; Drugs -- United States -- Patents; Intellectual property -- United States; Drug Industry; Intellectual Property; Drug Discovery; Pharmaceutical Preparations -- economics; Legislation, Drug; United States; LAW -- Intellectual Property -- General; Drug development; Drugs; Drugs -- Law and legislation; Intellectual property; Pharmaceutical policy; Pharmacy -- Law and legislation; United States; Urheberrecht; Pharmazeutische Industrie; Industrie pharmaceutique; History; Patents; Patents